Estimation of extracted from video record / Mohamad Yusof Mohamad Othman - Mohamad Othman, Mohamad Yusof (2020)
Vehicle tracking has been applied in traffic surveillance with the intention of gaining traffic flow information, capturing traffic violations, and classifying vehicles. Vehicle tracking is an undertaking that can open possibilities for countless other applications. Most traffic detectors in service today work based on inductive loops buried under the road surface. Vehicle speed estimation is very important for traffic management. Which can determine and calculate with video recording. Extraction video based computer vision has become a promising technology for real time supervision, monitoring and estimation speed vehicle movement in road. Especially considering significance of Intelligent Transportation System, the vision based supervision has the significant contribution, as it can facilitate real time monitoring, vehicle tracking and identification. This method is used speed calculation from video record for tracks the movement of vehicles with system computer. It is found that the estimation of speed achieved for accurately calculate vehicle speed. Vehicle speed calculated is the same as vehicle speed in real time. Vehicle speed accuracy can be recognized and verified by comparing GPS speedometer records.